Process engineering studies on synthesis of gold nanoparticles by Turkevitch method - Chakraborty, A. (Italian Association of Chemical Engineering - AIDIC, 2015)
Process design of a reactor for gold nanoparticle (AuNP) synthesis requires reaction rate data and an appropriate kinetic model. In the present work, rate parameters for AuNP synthesis by Turkevitch method were investigated. Influences of process conditions-molar ratio of reactants (chloroauric acid to trisodium citrate:0.33-5.32) and temperature (333-373 K) of reaction medium on kinetic parameters were studied. From an Arrhenius plot activation energy for AuNP synthesis reaction was estimated to be 21.69 Â±2.3 kJ/mol suggesting that precursor reduction occurred in aqueous phase followed by diffusion controlled nucleation and aggregation of reduced metals ions forming larger nanoparticles. Increase or decrease of molar ratio beyond the optimal range (M = 0.75-1.35) led to slower reaction rate, larger particle diameter and formation of AuNPs, which were unsuitable for biological applications. Copyright Â© 2015, AIDIC Servizi S.r.l.,.